Reducing the rate of fistula: does a fibrin sealant act as an adjunct in pharyngeal closure? A two-centre experience. Issue 7 (July 2020) - Bance, R Roplekar; Coyle, P; Dias, A; Kothari, P; Shah, K; Thaj, J; Vaz, F
Abstract: Background: Pharyngocutaneous fistula is a troublesome complication. Recently, synthetic materials such as fibrin sealant have been used as a secondary measure to treat fistula. This work assessed whether the primary use of fibrin sealant can reduce the rate of fistula. Method: A retrospective review of 50 cases from 2 centres was completed. Tisseel was an adjunct to primary closure in all cases. Results: In the first centre, 3 out of 34 cases developed pharyngocutaneous fistula (fistula rate of 9 per cent). All three were salvage cases. In the second centre, 0 out of 16 cases developed a fistula. Conclusion: The incidence of pharyngocutaneous fistula post-radiation and post-chemoradiotherapy in laryngectomy cases has been quoted as 23 per cent and 34 per cent respectively. This study represents the first patient series on the use of fibrin sealant as an adjunct in primary closure following laryngectomy. The results are promising, encouraging the use of Tisseel as an adjunct to meticulous closure.